Menyelidiki Kecemasan Berbahasa terhadap Pengalaman Komunikasi Pengguna dalam Free4Talk Edukatif: Sebuah Studi Psikolinguistik tentang Beragam Pendekatan Pembelajaran Bahasa Digital - Dita Efriani; M. Arif Rahman Hakim; Pebri Prandika Putra (Yayasan Sembilan Pemuda Indonesia, 2025)
This study aims to investigate the correlation between language anxiety and communication experiences among users of the Free4Talk platform in a digital language learning context. A quantitative correlational approach was utilized, involving 30 people chosen through purposive selection. Data was collected using two Likert-scale surveys. Upon examination of the instruments, 22 items were determined to be genuine and utilized in the study. Due to the data’s failure to satisfy the normalcy condition, Spearman’s rho was employed to examine the relationship between the variables. The findings indicated a negligible negative connection between linguistic anxiety and communication experience (r = –0.104). This indicates that elevated anxiety was marginally correlated with reduced communication experiences; however, this relationship was not statistically significant (p = 0.584). The findings suggest that language anxiety does not substantially affect users’ conversational experiences in peer-to-peer digital language learning settings, especially on the Free4Talk platform. Consequently, it may be deduced that elements beyond language anxiety may significantly influence learners’ communicative results in online language learning contexts. This study contributes to the limited quantitative research on language anxiety in peer-to-peer digital language learning platforms by offering empirical evidence.